Показники та методи оцінювання економічного потенціалу машинобудівних підприємств - Лесик, Лілія Іванівна (Національний університет "Львівська політехніка", 2015)
Дисертаційна робота присвячена розробці теоретико-методичних положень та практичних рекомендацій щодо формування і використання системи показників та методів оцінювання економічного потенціалу машинобудівних підприємств. Вперше запропоновано для вимірювання сукупного економічного потенціалу машинобудівних підприємств використовувати показник необхідної величини фінансових результатів від їх діяльності у майбутні періоди, за якої буде забезпечена мінімально допустима ефективність інвестицій, вкладених у матеріальні активи підприємств. Удосконалено систему показників ендогенного та екзогенного економічного потенціалу машинобудівних підприємств, метод оцінювання їх конкурентного потенціалу за видами продукції і метод обчислення ринкової вартості цих підприємств. Розвинуто типологію видів та чинників економічного потенціалу підприємств, а також засади утворення їх ринкової вартості. Диссертационная работа посвящена разработке теоретико-методических положений и практических рекомендаций по формированию и использованию системы показателей и методов оценки экономического потенциала машиностроительных предприятий. Впервые предложено для измерения совокупного экономического потенциала машиностроительных предприятий использовать показатель необходимой величины финансовых результатов от их деятельности в будущих периодах, при которой обеспечивается минимально допустимая эффективность инвестиций, вложенных в их материальные активы. Усовершенствовано систему показателей эндогенного и экзогенного потенциала машиностроительных предприятий, метод оценки их конкурентного потенциала по видам продукции и метод расчета рыночной стоимости. Получили развитие типология видов и факторов экономического потенциала предприятий, а также основы формирования их рыночной стоимости. Dissertation is devoted to the development and use of theoretical and methodological principles and practical recommendations for improvement of indicators and methods of evaluation of the economic potential of machine-building enterprises. The object of the study is evaluation process of the machine building enterprise’s economic potential. The subject of the study is theoretical, methodological and applicative provisions on the improvement of indicators system and methods of the economic potential of machine-building enterprises evaluation. Scientific novelty of the obtained results consists in development of theoretical and methodological standards and provides practical recommendations for the indicators and methods of evaluation of the economic potential of machine building enterprises improvement. For the first time for measuring the total economic potential of machine-building enterprises it was proposed to use the index of required value of the financial results from enterprises operations in future periods at which will be provided the minimum permissible effectiveness of investments in tangible assets in previous years. Application of the proposed index is caused by the considerations the decision of purchasing the property is correct if discounted at the time of purchase the actual value of the net cash flow from operating these assets is at least equal to the value of the initial capital invested in them. The system of the parameters of the machine building enterprises current level of endogenous and exogenous economic potential was improved. It has hierarchical structure, contains primary and secondary partial, comprehensive and general indicators and is based on the use of combined approach, whereby values of individual partial evaluation indexes are normalized, and others are optimized. It was established that processing the information required for the evaluation of endogenous and exogenous company’s economic potential should consider the hierarchical nature of the objective function, which in formalized form describes the purpose, the company aims to achieve. In particular, such a purpose may be the maximization of the company profits as a result of the full implementation of the relevant type of its potential in given time period. The method of assessment of the competitive potential of the machine-building company for certain types of machinery products, based on a selection of the best varieties for quality and the ratio of incurred expenses was worked out. It envisages the optimal amount of natural production and sales by the criterion of maximum possible superprofit considering the possible need for updating the equipment and technologies used in the enterprise. Herewith the magnitude of superprofit will be determined as the difference between the profit value and product of investments, that led him, on a minimum level of profitability.The method of the assessment of the value of total economic potential of engineering company by calculating its market value, which involves simultaneous use of individual components of income, comparative, and consumable approaches was improved. Using the proposed approach to the assessment of the market value of engineering enterprises, the integrated assessment of the value of its total economic opportunities may be obtained, as well as the directions for their implementation considering the planning process of the company’s activities may be established. A typology of economic potential of enterprises has been further developed. Comparing with the existing, it covers a number of additional typological criteria: the level of generalization potential objectives of the company; the availability of the required amount of resources and competencies to achieve its goals; time of achieving the enterprise’s relevant objectives; the degree of actual realization of economic potential; relation to the external environment of the company. It was extended the clustering factors of forming of the economic potential of enterprises on the basis of building a three-level model. According to which all these factors are divided into the following groups: primary factors; secondary factors which quantitative evaluation is based on information on the primary factors; summarizing factors which quantitative assessment is based on use of information on primary and secondary factors affecting the current level of economic potential of the company and use of appropriate methods for processing such information (e.g., optimization methods). The principles of the machine-building companies’ market value formation that provide selection of three types of factors – direct impact, indirect influence, and primary factors were developed. Such principles allow better describing of the patterns of economic opportunities formation of the business entity. Herewith the expected profit and predicted trend of change, risk premiums and liquidity in the rate of capitalization, risk-free discount rate and other allowances, which are included in the capitalization rate, were attributed to the direct impact factors, the magnitude of which ultimately determines the enterprise value. During the study such methods were applied: system analysis method (to study the factors determining the level of the economic potential of enterprises); generalization method (developing the evaluation method of the machine building companies’ market value); modeling method (to build mathematical models of strategic value of the economic potential of machine building companies); abstraction method (to develop methodical approach to the assessment of the current level of endogenous and exogenous potential of machine building enterprises); optimization method (used for the optimization of the volume of machinebuilding enterprises’ manufacturing production in assessing its competitive potential). The legislative and regulatory acts of Ukraine, scientific works of native and foreign authors, machine-building enterprises’ statistical reports, and online resources are theoretical and methodological basis of current research. The practical significance of the obtained results lies in the possibility of use of methodical recommendations on evaluation of the economic opportunities’ current and strategic levels by managers and economists of machine building enterprises.
Показатели и методы оценки экономического потенциала машиностроительных предприятий
Indicators and methods for assessing the economic potential of the machine-building enterprises
Keywords: економічний потенціал; машинобудівне підприємство; показник; метод; система; фінансовий результат; ринкова вартість; конкурентний потенціал; чинник; экономический потенциал; машиностроительное предприятие; показатель; метод; система; финансовый результат; рыночная стоимость; конкурентный потенциал; фактор; economic potential; machine building enterprise; index; method; system; financial result; market value; competitive potential; factor